1977
DOI: 10.1192/bjp.131.5.497
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia in Hawaii: Analysis of Cohort Mortality Risk in a Multi-ethnic Population

Abstract: Schizophrenic patients in treatment with the Hawaii state system have been followed from 1962 to 1972. This cohort includes 1,689 persons: out-patients as well as in-patients; of Japanese, Caucasian, part-Hawaiian, Filipino, Chinese and other ancestries. After ten years, 60 per cent remain registered with the Hawaii Mental Health Division; 14 per cent are found living in the state; 12 per cent are lost to follow-up; and 14 per cent have died. Mortality is analysed for all causes by comparison with similar ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Prevalence estimates were obtained from a range of population subgroups including elderly individuals ( n = 10; [52,70,71,101,108,121,149151,159]), ethnic groups ( n = 8; [58,134,139,140,166,199,213,218]), Aborigines ( n = 4; [105,106,115,164]), religious groups ( n = 5; [29,80,128,182,191]), homeless individuals ( n = 4; [118,161,192,194]), children and adolescents ( n = 3; [57,185,189]), students ( n = 2; [147,178]), twins ( n = 1; [61]), industrial workers ( n = 1; [172]), different castes ( n = 1; [145]), and an isolate pedigree ( n = 1; [99]).…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence estimates were obtained from a range of population subgroups including elderly individuals ( n = 10; [52,70,71,101,108,121,149151,159]), ethnic groups ( n = 8; [58,134,139,140,166,199,213,218]), Aborigines ( n = 4; [105,106,115,164]), religious groups ( n = 5; [29,80,128,182,191]), homeless individuals ( n = 4; [118,161,192,194]), children and adolescents ( n = 3; [57,185,189]), students ( n = 2; [147,178]), twins ( n = 1; [61]), industrial workers ( n = 1; [172]), different castes ( n = 1; [145]), and an isolate pedigree ( n = 1; [99]).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, borrowing from Lewine (1981) &dquo;differential timing model&dquo; of sex differences in age at onset of schizophrenic symptom seems to be firmly established. These findings do not strike us as unusual considering that Kraepelin (1971), Slater and Cowie (1971), Forrest and Hay (1972), Weiner and Marwit (1977) and Kramer (1978) had all reported the same.…”
Section: Discussionmentioning
confidence: 56%
“…As a continuous analysis of the data, following the footprints of Kraepelin (1971), Slater and Cowie (1971), Forrest and Hay (1972), Weiner and Marwit (1977) and Kramer (19'7~) who had been concerned with culture in their studies, we present research evidence of cultural effect on the sex differences in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Hirsch (1986) stated that the role of antidepressants in treatm ent for this group had not been definitively demonstrated; however, m ore recently Azorin (1994) reporting a prospective study demonstrated an improvement among patients with post-psychotic depression who had been treated with tricyclic antidepressants. Weiner & Marvit (1977) com ment on the attitudes of society and the related stigm a of m ental illness, as well as the attitudes of staff and fam ily. Interviews with patients have emphasised the centrality of eroded self-esteem in the suicidal schizophrenia patient .…”
Section: Anagem Ent Of Suicidal Patients With Schizophreniamentioning
confidence: 99%